PERSEPSI DAN EKSPEKTASI PESERTA DIDIK TERHADAP PELAKSANAAN LAYANAN KLASIKAL DI SMAK ABDI WACANA PONTIANAK TAHUN 2019/2020 - Rosmela Dwi Utari; Yuline Yuline; Indri Astuti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe classification of Guidance is called a basic service in Guidance and Counseling Because the rating Guide is the part that picks the biggest portion flat service Counseling at school. Various perceptions and expectations that arise in students both positive and negative perception greatly affect the results, interests and attitudes of learning so as to create an impression in receiving lessons. The general problem in this study is "How are the perceptions and expectations of students towards the implementation of classical services".The method used in this research is descriptive method with survey research and quantitative approach. Population of 34 students. This study uses indirect data collection techniques using questionnaires and documentation. The data analysis technique was carried out statistically using the percentage. Based on the results of data analysis shows that the perception of Abdi Wacana Pontianak SMAK students reached the category of "Pretty good" while the results of the analysis of the expectations of students towards the implementation of classical services that reached the category of "Good"Keywords: Perception, Expectations, Classical Services